2018
DOI: 10.1039/c7sc04724j
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of ultrafine metal-oxide nanoparticles within mesopores for biomass-derived catalytic applications

Abstract: A versatile strategy using MOFs as precursors to encapsulate ultrasmall non-noble metal-oxides nanoparticles in the mesopores of KIT-6 is developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 62 publications
(32 reference statements)
0
33
0
Order By: Relevance
“…To address this issue, heteroatom doping-such as N, S, B, O-can be introduced to the biomass-derived carbons by adding the heteroatom containing organic compounds either before or after the carbonization process [25,29,123]. On the other hand, nanocomposites of biomass-derived carbons with significantly enhanced energy density can also be obtained from the post-synthesis processes such as coating with conducting polymers and metal oxides [41,123,135].…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue, heteroatom doping-such as N, S, B, O-can be introduced to the biomass-derived carbons by adding the heteroatom containing organic compounds either before or after the carbonization process [25,29,123]. On the other hand, nanocomposites of biomass-derived carbons with significantly enhanced energy density can also be obtained from the post-synthesis processes such as coating with conducting polymers and metal oxides [41,123,135].…”
Section: Discussionmentioning
confidence: 99%
“…[80] In this work, an externalP ZS polymer shell was coatedo ntoaZIF-67 core. The polymer served as as ource for C, N, P, and S. TheZ IF-67 core is shown to be vital for the catalytic performance, as it plays the followingr oles:( 1) it behaves as as tructural template for the PZS coating and hence helps maintain the structural integrity of the hollow carbon shell duringt he pyrolysis process;( 2) the MOF aids in the generationo famesoporouss tructure, increasing the surfacea rea of NPS-HCS through the release of gases during the ZIF-67d ecomposition;( 3) the MOF increases the amounto fN -doping, optimizing the distribution of nitrogen species in the final NPS-HCS structure;( 4) the MOF improvest he wettability of the NPS-HCS in water; ( 5) the cobalt species in the ZIF-67 also promotest he graphitization of the carbon,w hich is vital for high selectivity.T he latter was supported by an additional experiment which showed that if the catalysts cores consist of mixed metal MOFs (ZnCo-ZIFs) or only Zn (such as ZIF-8), the result- [76] Copyright 2018R oyal SocietyofC hemistry.…”
Section: Metal-free Carbon Catalystsmentioning
confidence: 96%
“…Then, in 2018, Li‘s study placed a MOF precursor inside a mesoporous silica, known as KIT‐6. This led to ultrafine metal‐oxide NPs after subsequent calcination (Figure ) . Due to the oxide NPs being exclusively confined and uniformly distributed in the mesopores, particle aggregation and Co leaching were efficiently alleviated.…”
Section: Mof‐derived Catalystsmentioning
confidence: 99%
See 2 more Smart Citations